First Observations of the Disruption of the Earth's Foreshock Wave Field During Magnetic Clouds. Issue 22 (19th November 2019) - Turc, L.; Roberts, O. W.; Archer, M. O.; Palmroth, M.; Battarbee, M.; Brito, T.; Ganse, U.; Grandin, M.; Pfau‐Kempf, Y.; Escoubet, C. P.; Dandouras, I.
Abstract: The foreshock, extending upstream of Earth's bow shock, is a region of intense electromagnetic wave activity and nonlinear phenomena, which can have global effects on geospace. It is also the first geophysical region encountered by solar wind disturbances journeying toward Earth. Here, we present the first observations of considerable modifications of the foreshock wave field during extreme events of solar origin called magnetic clouds. Cluster's multispacecraft data reveal that the typical quasi‐monochromatic foreshock waves can be completely replaced by a superposition of waves each with shorter correlation lengths. Global numerical simulations further confirm that the foreshock wave field is more intricate and organized at smaller scales. Ion measurements suggest that changes in shock‐reflected particle properties may cause these modifications of the wave field. This state of the foreshock is encountered only during extreme events at Earth, but intense magnetic fields are typical close to the Sun or other stars. Plain Language Summary: Solar storms are giant clouds of particles ejected from the Sun into space during solar eruptions. When solar storms are directed toward Earth, they can cause large disturbances in near‐Earth space, for example, disrupting communications or damaging spacecraft electronics. Understanding in detail what happens when solar storms reach Earth is crucial to mitigate their effects. Using measurements from the Cluster spacecraft, we investigate how solar storms modify the properties of the very first region of near‐Earth space they encounter when journeying toward Earth. This region, called the foreshock, extends ahead of the protective bubble formed by the Earth's magnetic field, the magnetosphere. The foreshock is home to intense electromagnetic waves, and disturbances in this region can perturb the Earth's magnetosphere. Our study reveals that solar storms modify profoundly the foreshock, resulting in a more complex wave activity. Global numerical simulations performed with the Vlasiator code confirm our findings. These changes could affect the regions of space closer to Earth, for example, in modifying the wave properties or the amount of solar particles entering the Earth's magnetosphere. This needs to be taken into account to better anticipate the effects of solar storms at Earth. Key Points: When reaching geospace, magnetic clouds modify significantly the properties of the first geophysical region they encounter, the foreshock Typical quasi‐monochromatic foreshock waves are replaced by a superposition of waves at different periods with a shorter transverse extent Multiple field‐aligned beams observed during one event suggest a link between the multiple wave periods and the suprathermal ion properties